Psykologisen joustavuuden yhteys mielialaan ja kehollisiiin oireisiin pitkäkestoisesta uupumuksesta ja sisäilmaongelmista kärsivillä aikuisilla - Wikström, Liisa (2023)
Prolonged physical symptoms are significant burden for both society and those who suffer from them, and with a better understanding both health care operations and the everyday life of people can be improved. This study researched whether prolonged physical symptoms, fatigue and exhaustion and symptoms related to indoor air, have connection to mood. Further, the effect of psychological flexibility and its dimensions, openness to experience, behavioral awareness, and value-based actions, on both mood and physical symptoms was examined. The study is part of the larger Digipimo project and the research sample consisted of the project's intervention group (n=50). Mood was measured with PHQ9 and physical symptoms with PHQ15 self-assessment forms. Psychological flexibility and its dimensions were measured by using CompACT self-assessment questionnaire. There was no significant relationship between prolonged physical symptoms and mood, whereas better psychological flexibility was associated with both lower mood symptoms and physical symptoms. Acceptance of own feelings and thoughts, and self-meaningful activities were connected to both fewer mood symptoms and physical symptoms. Furthermore, the relationship status and the inclusion criterion influenced the connection between psychological flexibility and mood, but not the connection between psychological flexibility and physical symptoms. This thesis brought information especially about the connection of the dimensions of psychological flexibility with both mood and physical symptoms. By understanding the connections of psychological flexibility both as a whole and as separate dimensions, interventions can be planned in more detail and targeted at the dimension whose improvement affects the person's life the most.